TINJAUAN HUKUM TENTANG PEMBIAYAAN PADA BANK SYARIAH DI INDONESIA - Hasyim Lahilote (Jurnal Ilmiah Al-Syir'ah, 2006)
This research has been conducted in order to know the legal regulations concerning the Syariah Bank expenditure in Indonesia and the regulation of profit sharing at Bank syariah expenditure process according to Act Number 10, 1998. The result of the research indicates that the availability of the new Banking Law has opened a greater opportunity to the conventional banks in establishing new branches where their activities comprise among others, the performing of the expenditure activity based on the Syariah principle. Beside that, Act number 10, 1998 has become to Bank Syariah a legal umbrella in legitimating the syariah principles in the implementation of the bank operational system.